Agriculture and the economic transformation of Ethiopia - Mellor, John W.; Dorosh, Paul A. (International Food Policy Research Institute, 2010)
Economic development transforms an economy from one that is largely agricultural to one that is largely manufacturing and services. Since agriculture currently dominates Ethiopia's economy and employment, however, there is an issue as to what its role should be in getting from here to there. In the normal process of economic growth, non-agricultural sectors grow more rapidly than the agricultural sector. The slower growth of agriculture, its relative decline, concern about the difficulty of modernizing agriculture and pessimism about the potentials for technological change in agriculture suggest to some that agriculture should not be given priority for scarce resources in the interests of rapid overall growth. There is substantial evidence, however, that raising agricultural productivity is possible and that agricultural growth plays a key role in economic growth, particularly in low income countries. Moreover, the Government of Ethiopia is committed to rapid growth of agriculture as a means of accelerating the economic transformation and reducing poverty. This paper examines the implications of this commitment to both growth and reduction in poverty, analyzes the progress underway, and diagnoses the critical elements of change in policy required to reach the objectives. Combining a review of experiences of other developing countries with an analysis of growth multipliers for Ethiopia, the paper argues that a high rate of agricultural growth has far-reaching positive implications for increasing employment and accelerating poverty reduction. High agricultural growth also helps avoid the creation of megacities with large slum populations. In order to achieve this rapid agricultural growth with positive economy-wide linkages, however, it is necessary to engage "middle farmers", large enough to adopt new technologies and produce significant marketed surpluses, but small and numerous enough to have spending patterns that drive a vibrant rural non-farm sector. Finally, public and private investments in road, electricity and telecommunications are also needed to reduce marketing costs and enable growth in rural market towns and secondary cities, and provide social services to rural people. Maintaining a growth rate in agricultural GDP of six percent would provide enough employment growth to contribute to rapid economic transformation of the economy and rapid decline in poverty. Given the low level of crop yields relative to those of other countries with comparable resources, and relative to best farmers and experiment stations, a high rate of growth in agricultural productivity appears to be feasible. Current government policies are generally consistent with attaining continued high agricultural growth rates. However, reforms are needed to accelerate growth in seed production and distribution, and to improve fertilizer distribution and to accelerate growth in fertilizer use.